Dimensional Regularization Approach to the Renormalization Group Theory of the Generalized Sine-Gordon Model - Takashi Yanagisawa (Advances in Mathematical Physics)
We present the dimensional regularization approach to the renormalization group theory of the generalized sine-Gordon model. The generalized sine-Gordon model means the sine-Gordon model with high frequency cosine modes. We derive renormalization group equations for the generalized sine-Gordon model by regularizing the divergence based on the dimensional method. We discuss the scaling property of renormalization group equations. The generalized model would present a new class of scaling property.